POTENTIAL OF METAL MINERAL RESOURCES IN MOUNT GOGOREA WAHLUA FORMATION BURU ISLAND - Roberth B Riry (EDU SCIENCES JOURNAL, 2023)
Geologically, Buru Island is composed of quite varied rocks, both in the form of sedimentary rock, igneous rock and metamorphic rock produced by subduction and magmatism and sedimentation activities. This is why Buru Island has quite a variety of potential metal and non-metallic mineral resources. The Wahlua Formation is the most widely distributed rock formation on Buru Island, but until now the petrographic, geochemical characteristics, and potential geological and mineral resources in this formation have not been studied in detail. The aims of this study were (1) to obtain data on the petrographic and geochemical characteristics of the rocks at Mount Gogorea, and (2) to determine the potential of metal minerals at the Gogorea location. The research was carried out at 4 observation points and 4 rock sampling points. Identification of petrographic and mineral characteristics was carried out megascopically and microscopically. Rock geochemical data were obtained using the AAS and ICP OES methods. The main rocks that make up the Geology of Mount Gogorea in the Wahlua formation are light-colored quartzite, granuloblastic texture, and non-foliated structure, various colored schist (reddish-brown-fawn and dark gray), lepidoblastic texture, foliated-schistose structure with mica as constituent minerals, phyllite greenish-gray, brownish to light in color, crystalloblastic texture with a smooth surface, and foliated-phyllitic structure, minerals making up mica, quartz, chlorite, and dark gneic rocks (greenish gray, dark gray, dark green), granoblastic texture and foliated-gneissic structure, with minerals in quartz, mica and hornblende rocks. The levels of precious metal Au were 16.7 ppm and 16.4 ppm, Hg was 2.49 ppm, As was 17 ppm while the highest base metal content was Mn at 925 ppm. Potential metal minerals at the Mount Gogorea location include precious metals (Au, Hg and As) and base metals such as manganese, zinc, barium, lead, copper and nickel. The presence of Au elements in rocks is associated with the levels of other elements, namely Ba, Co, Cr, Cu, Fe, La, Mn, Ni, Pb, Sr, and Zn.